Polyurethane / small intestinal submucosa composite material as well as preparation method and application thereof

The polyurethane/small intestinal submucosal composite material was prepared by reacting asymmetric Janus membrane with crosslinking agent solution and using freeze-drying and impregnation and drying. The problem that existing materials cannot match the bladder mechanics of different species is solved, and the mechanical properties of the materials are realized Improve and biocompatibility optimization.

CN119424739AActive Publication Date: 2025-02-14WEST CHINA HOSPITAL SICHUAN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411569065.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing polyurethane/small intestinal submucosal composites cannot meet the mechanical matching of normal bladders in different species under different needs by adjusting the component ratio.

Method used

The polyurethane/small intestinal submucosal composite material was prepared by reacting asymmetric Janus films with crosslinking agent solution, and a polyurethane/small intestinal submucosal composite material was prepared by freeze-drying and impregnation and drying, forming a porous sponge and dense film with an asymmetric structure.

Benefits of technology

The mechanical properties of polyurethane/small intestinal submucosal composites have been significantly improved, and the proportion of components can be adjusted according to different needs, match the mechanical behavior of normal bladders in different species, and have excellent biocompatibility and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424739A_ABST
    Figure CN119424739A_ABST
Patent Text Reader

Abstract

The invention provides a polyurethane / small intestinal submucosa composite material as well as a preparation method and application thereof, and belongs to the field of medicines. According to the invention, the polyurethane / small intestinal submucosa composite material with an asymmetric structure is prepared by using different structural forms of the same component by using a freeze drying and dipping drying method. One side of the composite material is porous sponge, and the other side is a dense film, so that leakage can be effectively prevented on the basis of ensuring mechanical properties, and full-layer repair is performed. The proportion of the components of the composite material can be adjusted according to different requirements, so that the mechanical properties of the composite material are adjusted, and the composite material is matched with normal bladder mechanical behaviors of different species. The preparation method of the composite material is simple, convenient and high in generalizability, can be popularized to other polyurethane / extracellular matrix materials, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medicine, and in particular relates to a polyurethane / small intestinal submucosa composite material and a preparation method and application thereof. Background Art

[0002] In order to promote cell ingrowth and tissue regeneration, ideal soft tissue repair materials should have biocompatibility, excellent mechanical properties (such as tensile strength and resilience), and a suitable three-dimensional porous structure. At present, soft tissue repair materials are mainly divided into two categories: synthetic polymer materials and natural extracellular matrix. Synthetic materials have good physical and mechanical properties, but lack biological activity; while natural materials have biocompatibility and biological activity, but have problems such as poor resilience and easy collapse.

[0003] Among synthetic polymer materials, polyurethane (PU) is a polymer material widely used in the biomedical field. Among natural materials, small intestinal submucosa (SIS) is a natural extracellular matrix material with good biocompatibility and biodegradability, and has been widely used in tissue engineering.

[0004] Patent CN104341608B reports a polyurethane / small intestinal submucosa composite material, the preparation method of which includes the following steps: a. mixing anionic aqueous polyurethane emulsion and small intestinal submucosa powder, and vacuum freeze-drying to form; b. cross-linking, vacuum freeze-drying, and obtaining. However, the material cannot meet the mechanical matching with normal bladders of different species under different requirements by adjusting the proportion of components. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a polyurethane small intestinal submucosal composite material with significantly improved mechanical properties, and a preparation method and use thereof.

[0006] The present invention provides a polyurethane / small intestinal submucosal composite material, which is obtained by reacting an asymmetric Janus membrane with a crosslinking agent solution, washing, and drying;

[0007] The asymmetric Janus membrane is obtained by placing a polyurethane / small intestinal submucosa slice on top of a polyurethane / small intestinal submucosa solution for infiltration, followed by drying and sterilization;

[0008] The polyurethane / small intestinal submucosal solution is obtained by mixing polyurethane emulsion and small intestinal submucosal powder, wherein the mass ratio of polyurethane emulsion to small intestinal submucosal powder is 1 to 10:1;

[0009] The polyurethane / small intestinal submucosa slices are obtained by freeze-drying the polyurethane / small intestinal submucosa solution, rehydrating it, freezing it, and then slicing it.

[0010] Further, the crosslinking agent solution is obtained by mixing a buffer solution and a crosslinking agent; the buffer solution is a 2-morpholineethanesulfonic acid solution with a concentration of 20 to 40 mmol / L and a pH of 5 to 7, preferably a concentration of 30 mmol / L and a pH of 6.5; the crosslinking agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide;

[0011] The soaking temperature is 2-6°C, the time is 0.5-2h, preferably 4°C, and the time is 1h; the drying temperature is 25-35°C, the time is 20-30h, preferably 27°C, and the time is 24h;

[0012] The mixing conditions are: stirring at a speed of 400 to 600 rpm at 10 to 40° C. for 2 to 4 hours, preferably: stirring at a speed of 500 rpm at 15 to 35° C. for 3 hours;

[0013] The mass ratio of the polyurethane emulsion to the small intestinal submucosal powder is 2 to 8:1, preferably 6 to 8:1;

[0014] The freeze-drying conditions are: first storing at 0-5°C for 10 hours or more, then pre-freezing at -30--10°C for at least 10 hours, and freeze-drying for 20-30 hours, preferably: first storing at 4°C for 12 hours or more, then pre-freezing at -20°C for at least 12 hours, and freeze-drying for 24 hours;

[0015] The freezing conditions are: freezing at -90 to -70°C for at least 10 hours, preferably freezing at -80°C for at least 12 hours.

[0016] Furthermore, the polyurethane emulsion is prepared by the following method:

[0017] (1) Prepolymerization: reacting a hydroxyl donor, isocyanate and a catalyst to obtain a prepolymer;

[0018] (2) Chain extension: adding chain extender and organic solvent to the prepolymer and heating for reaction;

[0019] (3) Neutralization and emulsification: add alkali, stir well, then add water, alkali and organic solvent to the reaction system and stir;

[0020] (4) Purification: Concentrate under reduced pressure and dialyze against deionized water to obtain the product.

[0021] Furthermore, in step (1), the molar ratio of the hydroxyl donor to the isocyanate is 1:1 to 5;

[0022] The isocyanate is any one or more of isophorone diisocyanate, L-lysine diisocyanate, and diphenylmethane diisocyanate;

[0023] The hydroxyl donor is any one or more of polycaprolactone diol, polyethylene glycol, polytetrahydrofuran, propylene glycol, and 1,4-butanediol;

[0024] The catalyst is stannous octoate, triethanolamine or dibutyltin dilaurate;

[0025] The reaction temperature is 70-80°C and the reaction time is 2-4 hours;

[0026] In step (2), the molar ratio of the chain extender to the hydroxyl donor in step (1) is 0.5 to 3:1;

[0027] The chain extender is any one or more of 2,2-dihydroxymethylbutyric acid, 2,2-dihydroxymethylpropionic acid, N-methyldiethanolamine, and diethanolamine; the organic solvent is acetone;

[0028] The reaction temperature is 50-60°C and the reaction time is 2-4 hours;

[0029] In step (3), the volume mass ratio of the base to the chain extender in step (2) is 5-9:10-12; the stirring speed is 1200-1400 rpm, and the time is 1-3 hours;

[0030] The base is triethylamine or sodium hydroxide; the organic solvent is acetone.

[0031] Furthermore, in step (1), the molar ratio of the hydroxyl donor to the isocyanate is 1:3; the isocyanate is isophorone diisocyanate; the hydroxyl donor is polycaprolactone diol; the catalyst is stannous octoate; the reaction temperature is 74° C. and the reaction time is 3 hours;

[0032] In step (2), the molar ratio of the chain extender to the hydroxyl donor in step (1) is 1:1;

[0033] The chain extender is 2,2-dimethylolbutyric acid;

[0034] The reaction temperature is 54°C and the reaction time is 3 hours;

[0035] In step (3), the volume mass ratio of the base to the chain extender in step (2) is 7:11.11; the stirring speed is 1300 rpm, and the time is 2 hours;

[0036] The base is triethylamine.

[0037] Furthermore, the small intestinal submucosal layer powder is prepared by the following method:

[0038] 1) Cleaning and sorting: take the pig small intestine, clean it, and cut it into sections;

[0039] 2) Mechanical scraping: scrape the serosa, mucosa and muscle tissue, soak and clean with saline;

[0040] 3) Degreasing: After cleaning and drying, put it into a methanol / chloroform mixed solution for degreasing and cleaning;

[0041] 4) Digestion: Soak the cleaned pig small intestine in trypsin solution at 2-6°C for 10-15h and wash;

[0042] 5) Decellularization: Soak the material in a protein denaturing detergent solution for 2 to 6 hours and wash;

[0043] 6) Freeze-drying: flatten and freeze-dry for later use;

[0044] 7) Ball milling: After cutting into pieces, put them into a ball mill and grind them. Repeat 1 to 5 times.

[0045] Further, in step 4), the cleaned pig small intestine is immersed in a trypsin solution, treated at 4° C. for 12 h, and then cleaned;

[0046] In step 5), the material is immersed in a protein denaturing detergent solution for 4 hours;

[0047] In step 7), repeat 3 times.

[0048] The present invention also provides a method for preparing the polyurethane / small intestinal submucosa composite material, which comprises the following steps: reacting the asymmetric Janus membrane with a crosslinking agent solution, washing, and drying.

[0049] Furthermore, the reaction conditions are: reacting at 30-45° C. in the dark for 30-35 hours.

[0050] Furthermore, the reaction conditions are: reacting at 37° C. in the dark for 36 hours.

[0051] The present invention also provides use of the polyurethane / small intestinal submucosa composite material in preparing soft tissue repair materials.

[0052] The present invention has achieved the following beneficial effects:

[0053] 1. The present invention proposes for the first time to prepare a polyurethane / small intestinal submucosa composite material with an asymmetric structure by using a freeze-drying plus immersion drying method using different structural forms of the same component. The polyurethane / small intestinal submucosa composite material of the present invention has an asymmetric structure, one side is a porous sponge, and the other side is a dense membrane, which can effectively prevent leakage and perform full-layer repair while ensuring mechanical properties;

[0054] 2. In the polyurethane / small intestinal submucosa composite material of the present invention, polycaprolactone diol 1000 is used as a soft segment to synthesize polyurethane;

[0055] 3. The surface pores of the polyurethane / small intestinal submucosa composite material of the present invention are relatively consistent, which avoids the influence of pore size on cell function and facilitates cell growth and enrichment;

[0056] 4. The polyurethane / small intestinal submucosa composite material of the present invention exhibits excellent biocompatibility;

[0057] 5. The polyurethane / small intestinal submucosa composite material of the present invention can achieve a strain ratio of 50%-200%. The component ratio of the composite material can be adjusted according to different needs, and then its mechanical properties can be adjusted to match the mechanical behavior of normal bladders of different species and the contraction and filling changes of the bladders under normal physiological conditions of humans / pigs / rats. Among them, the PU / SIS6:1 group and the PU / SIS 8:1 group are most compatible with the mechanical behavior of normal bladders of humans and rats in physiological activities, and the mechanical properties are significantly improved;

[0058] 6. The polyurethane / small intestinal submucosa composite material of the present invention has excellent mechanical properties, and the tensile strength can reach above 1.5 MPa.

[0059] 7. The preparation method of the polyurethane / small intestinal submucosa composite material of the present invention is simple, convenient and has high scalability. It can be extended to other polyurethane / extracellular matrix materials and has good application prospects.

[0060] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0061] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 Preparation of PU / SIS (A: synthesis process route of PU; B: H-NMR spectrum of PU; C: preparation process diagram of PU / SIS; D: FTIR images of SIS, PU before and after cross-linking, and PU / SIS).

[0063] Figure 2Morphological characterization of PU / SIS composite materials: (A) Scanning electron microscope images of the composite materials obtained in Examples 1-4, from top to bottom, PU / SIS slices, sponge surface of integrated Janus material, dense membrane surface of integrated Janus material, and cross-section of integrated Janus material; (B) Water contact angle test images of dense membrane surface and sponge surface of integrated Janus material; Quantitative analysis of water contact angles of dense membrane surface (C) and sponge surface (D); (E) Swelling experiment.

[0064] Figure 3 The biocompatibility of PU / SIS composite materials with different ratios (smooth muscle cells were inoculated into PU / SIS composite materials. A: live-dead staining results; B: cytoskeleton staining results; C: scanning electron microscopy (SEM) results; D: hemolysis; E: statistical histogram of hemolysis rate).

[0065] Figure 4 Comparative data of the mechanical properties of materials in different proportions with pig bladder: (A) cyclic stretching; (B) elastic modulus; (C) ultimate strain; (D) ultimate stress; (E) stress-strain diagram of pig and (F) rat bladder with PU / SIS composite materials in different proportions; (G) nanoindentation.

[0066] Figure 5 Construction of finite element simulation model for repairing human and rat bladder defects with PU / SIS composite materials: Maximum stress (A) and maximum strain (B) of human bladder repaired with PU / SIS composite materials under normal internal pressure; Maximum stress (C) and maximum strain (D) of rat bladder repaired with PU / SIS composite materials. DETAILED DESCRIPTION

[0067] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.

[0068] The "room temperature" referred to in the present invention is 25±10°C, and "overnight" refers to 12±5 hours.

[0069] Example 1: Preparation of PU / SIS composite material

[0070] 1. Synthesis of water-based PU

[0071] (1) Prepolymer synthesis

[0072] Build a fixed support, heat the oil bath to 74°C, add polycaprolactone diol 1000 (PCL1000) (33.33 g, 33.33 mmol) and isophorone diisocyanate (IPDI) (21.48 g, 96.67 mmol) into a three-necked flask, pre-stir for 10 min in an oil bath, then drop stannous octoate (about 4 drops of 0.02 mL), continue stirring and reacting for 2 h 50 min to obtain a prepolymer. Observe the viscosity of the system during the reaction, add an appropriate amount of acetone to adjust the viscosity of the system if necessary, and visually observe that the viscosity of the reaction system that does not accumulate on the stirring rod during the stirring process is acceptable, so that the reaction is maintained in a stable state.

[0073] (2) Chain extension reaction

[0074] The prepolymer is cooled down (74℃→54℃), and 2,2-dihydroxymethylbutyric acid (DMBA) (4.94g, 33.33mmol) is weighed into another small single-necked flask and placed in the flask. 25ml of acetone is added and the flask is placed in a 54℃ oil bath to fully dissolve. The solution is slowly added to the prepolymer by a syringe (1ml / 5ml), and the reaction is continued by stirring for 3h. To ensure a smooth reaction, acetone can be used to adjust the viscosity of the system if necessary.

[0075] (3) Neutralization and emulsification

[0076] 1) Neutralization: Add triethylamine (TEA) (7 mL) into a three-necked flask and stir at room temperature for 20 min for neutralization.

[0077] 2) Emulsification: Take a 2L large beaker, add 200ml pure water, 14ml triethylamine, 50ml acetone, seal it with plastic wrap and tie it with a rubber band; put it under the stirring table, tear a small hole to put in the stirring paddle, adjust the speed to 1300rpm, slowly add the reaction product in the three-necked flask to the solution in the large beaker through a syringe, and stir it quickly for 2h to obtain PU emulsion.

[0078] (4) Purification

[0079] Use a 1L single-mouth bottle to remove acetone by rotary evaporation (half a day), then change water and dialyze for 2-3 days to remove small molecular organic residues to obtain a purified PU emulsion.

[0080] 2. Preparation of SIS powder

[0081] In the present invention, SIS powder is prepared by the following method:

[0082] 1) Cleaning and sorting: Take fresh pig small intestines, clean them, remove the surface grease, turn the small intestines inside out, clean them and cut them into intestinal segments about 10cm-25cm in length.

[0083] 2) Mechanical scraping: Scrape off the serosa, mucosa and muscle tissues, leaving only the porcine small intestinal submucosa (SIS), and soak it in physiological saline (0.9% NaCl 9g / 1000ml prepared with pure water) for repeated cleaning.

[0084] 3) Degreasing: The cleaned SIS is blotted dry with a wipe paper, and then placed in an equal volume of a methanol / chloroform mixture in a fume hood for degreasing overnight at room temperature. After sufficient degreasing, it is repeatedly washed until there is no organic solvent odor, and the SISI membrane is obtained.

[0085] 4) Digestion: The SIS membrane was immersed in a 0.25% trypsin solution (5 L PBS + 125 g trypsin) at 4° C. for 12 h, and then repeatedly rinsed with deionized water.

[0086] 5) Decellularization: Prepare a 0.5% (5L pure water + 25g SDS) SDS (sodium dodecyl sulfate) solution, soak the SIS membrane at room temperature for 4 hours, and wash repeatedly with deionized water to remove residual reagents.

[0087] 6) Freeze-drying: unfold the SIS membrane and flatten it, and freeze-dry it in a vacuum freeze dryer for later use.

[0088] 7) Ball milling: Cut the SIS membrane into small pieces as much as possible and put it into a ball mill. Repeat three times: put the ball mill into liquid nitrogen for 5 minutes to cool; ball milling speed 30 Hz, 5 minutes.

[0089] 8) Collect the SIS powder and store it at 4°C for later use.

[0090] 3. Preparation of PU / SIS composite materials

[0091] (1) Preparation of PU / SIS solution

[0092] SIS powder was added to the purified PU emulsion at a mass ratio of SIS powder to PU of 1:8, and stirred at 500 rpm for 3 h at room temperature to obtain a slightly viscous and uniform PU / SIS solution (wherein the PU solid content was 24 wt% and the SIS solid content was 3 wt%).

[0093] (2) Preparation of PU / SIS slices (also known as sponge layers)

[0094] 1) Inject 0.15 ml of the PU / SIS solution prepared in (1) into each hole of a silicone mold (circular silicone mold with a diameter of 1 cm and 1 ml per hole), first store at 4°C for 12 h (emulsion changes to jelly), then pre-freeze at -20°C for 12 h (jelly changes to ice), and freeze-dry for 24 h before use.

[0095] 2) The mixed material was rehydrated and frozen in a -80°C refrigerator for 12 h (until the material reached the state of ice cubes), and then frozen sliced ​​with a slice thickness of 300 μm / slice, and then washed and freeze-dried to obtain PU / SIS slices.

[0096] (3) Assembly of composite materials

[0097] The frozen PU / SIS slices were placed on top of the PU / SIS solution at 4°C for 1 hour to allow the bottom pores to be evenly infiltrated, and then placed in a 27°C oven for 24 hours to form an asymmetric Janus membrane by drying. The PU / SIS slice surface is called the sponge surface, and the other surface is called the dense membrane surface.

[0098] (4) EDC / NHS chemical crosslinking

[0099] Each piece of the asymmetric Janus membrane was immersed in twice the volume of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride / N-hydroxysuccinimide (EDC / NHS) crosslinking solution with a pH of 6.5, and reacted at 37°C in the dark for 36 hours. Then, it was washed once with saturated saline, each time for at least 30 minutes, and washed at least 5 times with a large amount of deionized water, each time for at least 30 minutes, and then dried and sterilized with ethylene oxide to obtain a PU / SIS composite material (also known as an integrated Janus material).

[0100] The cross-linking solution was prepared as follows:

[0101] Use pure water to dissolve 2-morpholineethanesulfonic acid (MES) to prepare a 30mmol / L MES solution, use Tris aqueous solution to adjust the pH of the buffer solution to about 6.5, weigh 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) in a mass ratio of 1:2.5, add and mix to obtain a cross-linking solution. Control that 1g EDC is contained in every 40ml of the cross-linking solution.

[0102] Example 2: Preparation of PU / SIS composite material

[0103] The method of Reference Example 1 is different in that, when preparing the PU / SIS composite material, SIS powder is added to the purified PU emulsion at a mass ratio of 1:6 to obtain a PU / SIS solution with a PU solid content of 18wt% and a SIS solid content of 3wt%, and then the composite material is prepared.

[0104] Example 3: Preparation of PU / SIS composite material

[0105] The method of Reference Example 1 is different in that, when preparing the PU / SIS composite material, SIS powder is added to the purified PU emulsion at a mass ratio of 1:4 to obtain a PU / SIS solution with a PU solid content of 12wt% and a SIS solid content of 3wt%, and then the composite material is prepared.

[0106] Example 4: Preparation of PU / SIS composite material

[0107] The method of Reference Example 1 is different in that, when preparing the PU / SIS composite material, SIS powder is added to the purified PU emulsion at a mass ratio of 1:2 to obtain a PU / SIS solution with a PU solid content of 6wt% and a SIS solid content of 3wt%, and then the composite material is prepared.

[0108] The beneficial effects of the present invention are demonstrated by experimental examples below.

[0109] Experimental Example 1: Structural Characterization of the PU / SIS Composite Material of the Present Invention

[0110] 1. Experimental methods

[0111] The 1H-Nuclear magnetic resonance spectroscopy ( 1 H-NMR) was used to characterize the chemical structure of PU, Fourier transform infrared spectroscopy (FTIR) was used to analyze the structure of PU / SIS composite materials, and attenuated total reflection (ATR) was used to test SIS, PU before and after cross-linking, and PU / SIS. The scanning wave number range was 1000-3600 cm -1 .

[0112] Surface and cross-sectional morphology of materials obtained by scanning electron microscopy: Scanning electron microscopy (SEM) was used to characterize the surface and cross-sectional morphology of PU / SIS composites. After pretreatment, the samples were surface treated by metal coating process to improve conductivity and imaging quality. SEM was used to observe the pore size, distribution and microstructure of the samples.

[0113] The hydrophilicity of the material is obtained and quantitatively analyzed through the water contact angle experiment: The hydrophilicity of the PU / SIS composite material is tested using a contact angle meter. The hydrophilicity of the material is evaluated by dropping deionized water on the surface of the material and recording the contact angle between the water droplet and the material surface. The contact angle of at least five different positions of each group of materials is measured, and the average value is calculated for quantitative analysis. Materials with a contact angle of less than 90° are considered hydrophilic materials. The smaller the contact angle, the stronger the hydrophilicity of the material. The swelling characterization of the material is obtained through the swelling experiment: the material sample is soaked in deionized water for a certain period of time, taken out and weighed after absorbing the surface moisture with filter paper, and the swelling of the material is measured. The swelling ratio is calculated by the formula (Ws-Wd) / Wd×100(W_s-W_d) / W_d\times100%(Ws-Wd) / Wd×100, W_s is the weight after soaking, and W_d is the weight when dry. The swelling performance of the composite material is characterized by measuring the swelling rate at different time periods.

[0114] 2. Experimental results

[0115] Figure 1 A and 1C are the synthetic process route of PU and the preparation process diagram of PU / SIS composite materials, respectively. Figure 1 B) and FTIR images ( Figure 1 D) Confirmed the successful preparation of PU and PU / SIS, respectively.

[0116] H NMR ( Figure 1 B) Analysis showed that the signal peaks at 0.85-0.97 ppm corresponded to the chemical shifts of DMBA methyl protons and IPDI methyl protons, confirming the existence of these monomers; the peaks at 3.99 ppm (-COOCH2-), 2.27 ppm (-CH2COO-), 1.55 ppm (-CH2CH2CH2-) and 1.29 ppm (-CH2CH2CH2-) were attributed to the methylene protons of the PCL segment, indicating the successful introduction of the PCL segment; in addition, the signal peaks at 4.00-4.21 ppm were attributed to the methylene protons (-NHCOO-CH2-) formed by the reaction of PCL and DMBA with isocyanate, further verifying the successful construction of the polyurethane structure.

[0117] FTIR spectra of SIS, PU before and after cross-linking, and PU / SIS ( Figure 1 D) Display: 1651cm -1 The absorption peak at 1651 cm is the stretching vibration peak of C=O in the carbamate group. -1 The absorption peak appearing at is the characteristic absorption peak of the amide bond formed by EDC / NHS cross-linking of the composite material, indicating that a chemical reaction occurred in PU / SIS under the action of the cross-linking agent.

[0118] Scanning electron microscopy (SEM) results ( Figure 2 A) shows that the PU / SIS slices show a trend of gradually decreasing pore size with the increase of polyurethane (PU) solid content. However, the surface pore size of composite materials with different proportions is relatively consistent, concentrated between 30 and 60 microns. This shows that the preparation method of the present invention can effectively control the surface pores of materials with different ratios, making the pore size relatively uniform. This consistency avoids the negative impact that the pore size may have on cell function, and contributes to the uniform attachment and proliferation of cells. The porous structure provides an ideal microenvironment for cell adhesion and growth, and promotes the enrichment and proliferation of cells on the surface of the material.

[0119] Water contact angle test results ( Figure 2 BD) shows that the water contact angles of all PU / SIS composites are less than 90 degrees, indicating that the materials have good hydrophilicity. Hydrophilic materials are generally more conducive to cell adhesion and expansion, which is particularly important for the application of biomedical materials, especially in promoting the interaction between cells and materials.

[0120] In addition, the swelling rate test results ( Figure 2 E) shows that the swelling rate of each group of composite materials is low, which has a positive effect on maintaining the mechanical properties of the material. The lower swelling rate helps prevent the material from over-expanding in body fluids, thereby maintaining its structural strength and stability.

[0121] These properties collectively indicate that the pore size of the surface of the PU / SIS composite material of the present invention is relatively consistent, which is conducive to the uniform attachment and proliferation of cells, helps to promote the enrichment and proliferation of cells on the surface of the material, has good hydrophilicity and structural stability, and is an ideal tissue repair material.

[0122] Experimental Example 2: Biocompatibility test of the PU / SIS composite material of the present invention

[0123] 1. Experimental methods

[0124] The biocompatibility of the composite material was tested through cell live-death experiment, cytoskeleton experiment and scanning electron microscopy experiment.

[0125] (1) Cell live / dead assay

[0126] In order to evaluate the cytotoxicity of PU / SIS composite materials, the Live / Dead double staining method was used to detect the cell activity of the materials. The sterilized materials were placed at the bottom of a 24-well plate, hydrated with SMC medium, inoculated with smooth muscle cells, and the medium was changed regularly. The materials were taken out at 3 and 5 days, respectively, and live and dead cells were stained with propidium iodide (PI) and calcein AM dyes. The cell morphology was observed by two-photon confocal microscopy, with the FITC channel showing live cells (green fluorescence) and the TRITC channel showing dead cells (red fluorescence). By analyzing the live / dead cell ratio at different time points, the direct toxicity and cell activity of the material can be evaluated.

[0127] (2) Cytoskeleton staining experiment

[0128] To further explore the cell status on PU / SIS materials, a cytoskeleton staining experiment was conducted. Smooth muscle cells were inoculated on sterilized PU / SIS materials and stained on the 3rd and 5th days, respectively. After cell fixation, the cells were permeabilized and stained with CY5-labeled phalloidin to observe the actin filaments in the cytoskeleton. The CY5 channel (excitation wavelength 640nm) of the laser confocal microscope displayed the cytoskeleton structure (red fluorescence signal) and analyzed the adhesion, proliferation and morphological changes of cells on the material surface.

[0129] (3) Scanning electron microscopy experiment

[0130] In order to further study the growth state of cells on PU / SIS composite materials, scanning electron microscopy (SEM) was used to characterize the cells on the materials. After the materials were inoculated with smooth muscle cells, they were fixed and freeze-dried on the 3rd and 5th days respectively. Subsequently, the samples were sprayed with gold and observed using a field emission scanning electron microscope.

[0131] (4) Hemolysis test

[0132] In the hemolysis experiment, the material to be tested was first sterilized and pretreated in PBS at 37 degrees for 30 minutes. After collecting the anticoagulated rabbit whole blood and centrifuging the supernatant, it was repeatedly washed and centrifuged with PBS solution, and then diluted to 5% rabbit diluted blood. The diluted blood was added to each sample, the positive control group was 1% Tritionx-100, and the negative control group was PBS, and incubated at 37°C for 1 hour. After the incubation, the supernatant was centrifuged and separated, and the absorbance was measured at a wavelength of 545nm using a spectrophotometer. The hemolysis rate was calculated by comparison with the positive and negative control groups to evaluate the blood compatibility of the material.

[0133] 2. Experimental results

[0134] Live / Dead staining results ( Figure 3A) shows that all components of PU / SIS composite materials exhibit good biocompatibility. Live cells (green fluorescence) are dominant, and dead cells (red fluorescence) are very few, indicating that the cytotoxicity of the material is low. The survival rate of smooth muscle cells on the surface of the material is high. With the extension of culture time, the number of live cells increases significantly, showing that the material has a good support effect on cell proliferation, proving that the PU / SIS composite material has strong cell compatibility.

[0135] Cytoskeleton staining results ( Figure 3 B) The biocompatibility of the PU / SIS composite material was further verified. The actin filaments (red fluorescence) in the cytoskeleton were clearly visible, and the cell morphology was good, indicating that the cells had good adhesion and spreading on the surface of the material. As the culture time increased, the distribution of the cytoskeleton became more dense, indicating that the cells proliferated well on the PU / SIS material, further proving that the material has the ability to promote cell adhesion and proliferation.

[0136] Scanning electron microscopy (SEM) results ( Figure 3 C) shows that a large number of smooth muscle cells grow on the surface of all PU / SIS composites. The cell morphology is intact and the ductility is good, indicating that the porous structure of the material surface is conducive to the growth and proliferation of cells. The microstructure of the material provides a good attachment environment for cells, further supporting its biocompatibility.

[0137] Hemolysis experiments were performed to evaluate whether the PU / SIS composite material would cause red blood cell rupture, and to determine the effects of the composite material on blood components, including red blood cells, complement system, coagulation proteins, and the activities of different enzymes. Figure 3 D, E) show that the hemolysis rate of each PU / SIS ratio is less than 5%, which has good blood compatibility.

[0138] Based on the above results, PU / SIS composites can effectively promote cell adhesion and proliferation and show excellent biocompatibility.

[0139] Experimental Example 3: Mechanical matching test between the PU / SIS composite material of the present invention and normal bladder

[0140] 1. Experimental methods

[0141] The stress-strain curves, ultimate stress and ultimate strain of the composite material and pig bladder and rat bladder were obtained by in vitro passive dynamics test using a universal mechanical tensile instrument;

[0142] Bladder dynamic mechanical properties testing: Normal pig and rat bladders and each group of PU / SIS scaffold materials were prepared into 75x4x2mm, 20x4x2mm, and 20x4x2mm strip specimens. Three samples were taken from each group and cyclic tensile and uniaxial tensile tests were performed using a universal mechanical testing system.

[0143] Cyclic tensile test: at room temperature, the tensile rate is 10 mm / min, the tensile strain is 50% of the sample length, and the number of cycles is 10. Uniaxial tensile test: at room temperature, the tensile rate is 10 mm / min, the clamping length is 10 mm, and the tensile strength, tensile modulus and elongation at break of each sample are tested.

[0144] Obtaining the surface micro-stiffness of composite materials through nano-indentation experiments: Use a nano-indenter to measure the surface micro-stiffness of PU / SIS composite materials. By analyzing the indentation data, the mechanical parameters such as the Young's modulus of the material are calculated.

[0145] Finite element analysis was used to establish simulation models of human and mouse repair: Based on MRI image data, Mimics software was used to reconstruct a three-dimensional model of a healthy bladder. Combined with in vitro passive dynamics data, ANSYS software was used to establish finite element simulation models of a healthy bladder and a bladder repaired with composite materials to obtain the stress-strain distribution during the material repair process.

[0146] 2. Experimental results

[0147] The mechanical properties of PU / SIS composites were evaluated by in vitro passive dynamics tests. Pig bladder, mouse bladder and PU / SIS composites were selected for the experiment. The experiment first subjected the bladder tissue and composites to 10 cycles of stretching and uniaxial stretching to obtain their stress-strain curves. The stress-strain curves produced by cyclic stretching can reflect the viscoelastic properties of the material. The results ( Figure 4 A) The curves showing that the PU / SIS 4:1 and PU / SIS 6:1 groups are closest to the mechanical behavior of normal porcine bladder.

[0148] As the PU solid content increases, the mechanical properties of the material show an upward trend. The elastic modulus of the PU / SIS2:1 group is significantly lower than that of the porcine bladder, while the elastic modulus of the PU / SIS 8:1 group is significantly higher than that of the porcine bladder. In contrast, the elastic modulus of the PU / SIS 4:1 and PU / SIS 6:1 groups are not significantly different from those of the porcine bladder, indicating that these two groups of composite materials match the porcine bladder in terms of elasticity ( Figure 4 B). In addition, the ultimate stress and ultimate strain of the PU / SIS 8:1 group were not significantly different from those of porcine bladder ( Figure 4 C, D).

[0149] The slope of the stress-strain curve increases with the increase of PU solid content, indicating that the ultimate stress and ultimate strain increase accordingly. This result shows that PU / SIS composite materials can achieve mechanical matching with pig bladder and mouse bladder by adjusting different proportions of PU and SIS ( Figure 4 E, F). Nanoindentation test results ( Figure 4 G) is consistent with the above findings and further verifies the mechanical properties of different PU / SIS composites.

[0150] Based on MRI image data and uniaxial tensile and cyclic tensile experimental data, a finite element simulation model of healthy bladder and repaired bladder was established ( Figure 5 AD) to simulate and compare the deformation behavior of healthy bladder and repaired bladder under physiological load. Finite element analysis can effectively evaluate the biomechanical compatibility of different PU / SIS composite materials in the human body. The results show that the simulation results of PU / SIS 6:1 group and PU / SIS 8:1 group are most consistent with the mechanical behavior of normal bladder in human and rat during physiological activities, especially in the bladder filling and contraction stages. These two groups of materials can well simulate the deformation characteristics and load-bearing capacity of normal bladder.

[0151] The above experimental results indicate that the polyurethane / small intestinal submucosa composite material prepared by the present invention can achieve a strain ratio of 50%-200%, and the component ratio of the composite material can be adjusted according to different needs, thereby adjusting its mechanical properties to match the normal bladder mechanical behavior of different species and the contraction and filling changes of the bladder under the normal physiological state of humans / pigs / rats. Among them, the PU / SIS 6:1 group and the PU / SIS 8:1 group are most consistent with the mechanical behavior of the normal bladder of humans and rats in physiological activities, and the mechanical properties are significantly improved.

[0152] In summary, the present invention provides a polyurethane / small intestinal submucosa composite material, and a preparation method and use thereof. The present invention uses a freeze-drying plus impregnation drying method to prepare a polyurethane / small intestinal submucosa composite material with an asymmetric structure using different structural forms of the same component. The composite material has a porous sponge on one side and a dense membrane on the other side, which can effectively prevent leakage and perform full-layer repair on the basis of ensuring mechanical properties. The composite material can adjust the component ratio according to different needs, and then adjust its mechanical properties to match the normal bladder mechanical behavior of different species. The preparation method of the composite material of the present invention is simple, convenient, and highly scalable. It can be extended to other polyurethane / extracellular matrix materials and has good application prospects.

Claims

1. A polyurethane / small intestinal submucosa composite material, characterized in that: It is obtained by reacting an asymmetric Janus membrane with a crosslinking agent solution, washing, and drying; The asymmetric Janus membrane is obtained by placing a polyurethane / small intestinal submucosa slice on top of a polyurethane / small intestinal submucosa solution for infiltration, followed by drying and sterilization; The polyurethane / small intestinal submucosal solution is obtained by mixing polyurethane emulsion and small intestinal submucosal powder, wherein the mass ratio of polyurethane emulsion to small intestinal submucosal powder is 1 to 10:1; The polyurethane / small intestinal submucosa slices are obtained by freeze-drying the polyurethane / small intestinal submucosa solution, rehydrating it, freezing it, and then slicing it.

2. The polyurethane / small intestinal submucosa composite material according to claim 1, characterized in that: The crosslinking agent solution is obtained by mixing a buffer solution and a crosslinking agent; the buffer solution is a 2-morpholineethanesulfonic acid solution with a concentration of 20-40 mmol / L and a pH of 5-7, preferably a concentration of 30 mmol / L and a pH of 6.5; the crosslinking agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide; The soaking temperature is 2-6°C, the time is 0.5-2h, preferably 4°C, and the time is 1h; the drying temperature is 25-35°C, the time is 20-30h, preferably 27°C, and the time is 24h; The mixing conditions are: stirring at a speed of 400 to 600 rpm at 10 to 40° C. for 2 to 4 hours, preferably: stirring at a speed of 500 rpm at 15 to 35° C. for 3 hours; The mass ratio of the polyurethane emulsion to the small intestinal submucosal powder is 2 to 8:1, preferably 6 to 8:1; The freeze-drying conditions are: first storing at 0-5°C for 10 hours or more, then pre-freezing at -30--10°C for at least 10 hours, and freeze-drying for 20-30 hours, preferably: first storing at 4°C for 12 hours or more, then pre-freezing at -20°C for at least 12 hours, and freeze-drying for 24 hours; The freezing conditions are: freezing at -90 to -70°C for at least 10 hours, preferably freezing at -80°C for at least 12 hours.

3. The polyurethane / small intestinal submucosa composite material according to claim 2, characterized in that: The polyurethane emulsion is prepared by the following method: (1) Prepolymerization: reacting a hydroxyl donor, isocyanate and a catalyst to obtain a prepolymer; (2) Chain extension: adding chain extender and organic solvent to the prepolymer and heating for reaction; (3) Neutralization and emulsification: add alkali, stir well, then add water, alkali and organic solvent to the reaction system and stir; (4) Purification: Concentrate under reduced pressure and dialyze against deionized water to obtain the product.

4. The polyurethane / small intestinal submucosa composite material according to claim 3, characterized in that: In step (1), the molar ratio of the hydroxyl donor to the isocyanate is 1:1 to 5; The isocyanate is any one or more of isophorone diisocyanate, L-lysine diisocyanate, and diphenylmethane diisocyanate; The hydroxyl donor is any one or more of polycaprolactone diol, polyethylene glycol, polytetrahydrofuran, propylene glycol, and 1,4-butanediol; The catalyst is stannous octoate, triethanolamine or dibutyltin dilaurate; The reaction temperature is 70-80°C and the reaction time is 2-4 hours; In step (2), the molar ratio of the chain extender to the hydroxyl donor in step (1) is 0.5 to 3:1; The chain extender is any one or more of 2,2-dihydroxymethylbutyric acid, 2,2-dihydroxymethylpropionic acid, N-methyldiethanolamine, and diethanolamine; the organic solvent is acetone; The reaction temperature is 50-60°C and the reaction time is 2-4 hours; In step (3), the volume mass ratio of the base to the chain extender in step (2) is 5-9:10-12; the stirring speed is 1200-1400 rpm, and the time is 1-3 hours; The base is triethylamine or sodium hydroxide; the organic solvent is acetone.

5. The polyurethane / small intestinal submucosa composite material according to claim 4, characterized in that: In step (1), the molar ratio of the hydroxyl donor to the isocyanate is 1:3; the isocyanate is isophorone diisocyanate; the hydroxyl donor is polycaprolactone diol; the catalyst is stannous octoate; the reaction temperature is 74° C. and the reaction time is 3 hours; In step (2), the molar ratio of the chain extender to the hydroxyl donor in step (1) is 1:1; The chain extender is 2,2-dimethylolbutyric acid; The reaction temperature is 54°C and the reaction time is 3 hours; In step (3), the volume mass ratio of the base to the chain extender in step (2) is 7:11.11; the stirring speed is 1300 rpm, and the time is 2 hours; The base is triethylamine.

6. The polyurethane / small intestinal submucosa composite material according to claim 1, characterized in that: The small intestinal submucosal layer powder is prepared by the following method: 1) Cleaning and sorting: take the pig small intestine, clean it, and cut it into sections; 2) Mechanical scraping: scrape the serosa, mucosa and muscle tissue, soak and clean with saline; 3) Degreasing: After cleaning and drying, put it into a methanol / chloroform mixed solution for degreasing and cleaning; 4) Digestion: Soak the cleaned pig small intestine in trypsin solution at 2-6°C for 10-15h and wash; 5) Decellularization: Soak the material in a protein denaturing detergent solution for 2 to 6 hours and wash; 6) Freeze-drying: flatten and freeze-dry for later use; 7) Ball milling: After cutting into pieces, put them into a ball mill and grind them. Repeat 1 to 5 times.

7. A method for preparing the polyurethane / small intestinal submucosa composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: reacting the asymmetric Janus membrane with a cross-linking agent solution, washing, and drying.

8. The method according to claim 7, characterized in that The reaction conditions are: react at 30-45° C. in the dark for 30-35 hours.

9. The method according to claim 8, characterized in that The reaction conditions are: reaction at 37° C. in the dark for 36 h.

10. Use of the polyurethane / small intestinal submucosa composite material according to any one of claims 1 to 6 in the preparation of soft tissue repair materials.

Citation Information

Patent Citations

  • Preparation method of polyurethane / small intestinal submucosa composite material

    CN104341608B

  • Asymmetric double-crosslinked composite material, as well as preparation method and application of same

    CN102648987A

  • Capsule polyurethane drug controlled release body with temperature control switch, and preparation method thereof

    CN103223173A

  • Polyurethane (PU) / small intestine submucosa (SIS) membrane composite material and application thereof

    CN104312140A

  • In-vivo degradable and absorbable artificial medical tissue repairing film

    CN104414772A